Worship Wars! : cultural transition of praise and worship in Chinese dialect-based churches of tradition denomination in Singapore - Chang, Dorcas Ping (2015)
This paper studies the cultural transition of Praise and Worship (P&W) in Chinese dialect-based churches of Traditional denomination in Singapore. Using a Teow Choo Baptist Church as a case study, the cultural transition from Traditional to Contemporary P&W is critically analysed using Macionis’ Five Components of Culture and Bourdieu’s concept of Habitus, Capitals and Field. By examining the cultural elements and attached meanings propelling the transition, this paper hope to highlight the complex power struggle in the religious sphere of cultural practices.